Expansion Of Asnaf Gharimin’s Interpretation In A Pandemic Context In Malaysia - Azman Ab Rahman; Nur Wahida Lokman; Md. Yunus Abd Aziz; Muhamad Firdaus Ab Rahman; Hussein 'Azeemi Abdullah Thaidi (Usuli Faqih Research Centre, 2024)
Indexed by MyCite